Diyanet İşleri Başkanlığı’nın kurumsal varlığına ve meşruiyetine yönelik eleştirel söylemler üzerine analiz - Dalmış, Emine (My University, 2022)
Diyanet İşleri Başkanlığı, Türkiye’ye özel bir tecrübesinin sonucunda kurulmuş bir kurumdur. Osmanlı devlet yapılanmasında Şeyhülislamlık kurumu bazı gerekçelerle kaldırılmış, yerine Şer’iye ve Evkaf Vekâleti ihdas edilmiştir. Dört yıl kadar kısa bir süre sonra 3 Mart 1924 yılında Şer’iye ve Evkaf Vekâleti ilga edilip yerine Diyanet İşleri Reisliği kurulmuştur. Böyle bir kurumun kurulmasının sebepleri her ne kadar toplumsal bir ihtiyacın karşılanması ve oluşacak toplumsal tepkileri engellemek olsa da laikliği kurucu ilke kabul eden bir devletin bir birimi olması bazı tartışmalara neden olmuştur. Bu eleştiriler ilk olarak Cumhuriyetin kurucu kadrosu ve savunucuları tarafından gelmiştir. Kuruma eleştiri getiren diğer gruplar arasında İslamcılar ve Aleviler sayılabilir. Ulusal Tez Merkezi (https://tez.yok.gov.tr/ UlusalTezMerkezi/ giris.jsp) üzerinde yapılan literatür taraması sonucunda Diyanet İşleri Başkanlığı’nın kurumsal varlığı, teşekkül dönemi ve şekli, ara dönemlerde kurumun durumu, kurum bağlamında din-devlet ilişkileri alanında bazı çalışmalar yapıldığı görülmüştür. Fakat bizim ele almayı düşündüğümüz şekliyle Diyanet İşleri Başkanlığı’nın kurumsal varlığına ve meşruiyetine dair yeteri kadar çalışma yapılmadığı hatta yapılan çalışmaların çok dağınık olduğu ve belirli bir döneme yoğunlaştığı göze çarpmaktadır. Bu çalışmanın amacı ise kurumun kuruluş şartlarını görmeyi ve bu şartlar içinde kurulan kuruma özellikle 1980 sonrasında yoğunlaşan eleştirilerin neler olduğunu, yapılan eleştirilerin kimler tarafından hangi gerekçelerle yapıldığını, bugün hala devam eden eleştirilerin bir kısmının neden bir cevap bulmadığını görmeye çalışmaktır. Çalışmamızın önemi tam olarak burada ortaya çıkmaktadır. Söz konusu Diyanet İşleri Başkanlığı ve özellikle ona yapılan eleştiriler olunca yapılan çalışmalar objektiflik kaygısı gütmekten ziyade uzak, taraflı bir dille yazıldığı görülmektedir. Bizim bu çalışmada yapmak istediğimiz Diyanet İşleri Başkanlığı’na çeşitli nedenlerden dolayı yapılan eleştirileri tarafsız bir gözle okumayı, anlamayı ve yorumlamayı amaçlamaktayız. Bundan dolayı yapılan eleştirileri takip etmek için meclis tutanakları, kurumun yıllık raporları, kurum içi ve dışı yazışmalar, tartışmaların medyaya (gazete, haber bültenleri vb) yansımaları ve kuruma dair yapılan diğer çalışmalar takip edilecektir. Böylece eleştirileri, mümkün olduğunca kendi gerçek zaman ve şartlarında görmek ve araştırma konusu olan eleştirilerin farklı gruplar tarafından nasıl görülmüş ve nereye konmuş olduğunu izlemek mümkün olacaktır.

The Presidency of Religious Affairs is an institution founded as a result of Turkey’s own particular experience. The Sheikh-ul-Islam institution which was an institution of the Ottoman state structure was abolished for some reasons, and the Ministry of Sharia and Foundations (Awqaf) was created instead. After a short period of four years, on March 3, 1924, the Ministry of Shar’iyyah and Foundations was abolished and the Presidency of Religious Affairs was established in its place. For the establishment of the institution, although there were such plausible reasons as the purpose of meeting a social need and preventing the social reaction that will occur, its existence as a unit of the state within a system that accepts secularism as a founding principle had brought some controversies. These criticisms first came from the founding staff of the Republic and the defenders of them. Other groups critical of the institution include Islamists and Alawites. Based on a literature review through National Thesis Center of Turkey (https://tez.yok.gov.tr/ UlusalTezMerkezi/ giris.jsp adresi üzerinden) it is apparent that some studies were conducted on institutional existence of the Presidency of Religious Affairs, the period and style of its formation, the position of the institution in the interim periods and the relationship between religion and state in the context of the institution. However, it has been observed that there is not enough work done on the institutional existence and legitimacy of the Presidency of Religious Affairs as we have discussed, and even the given studies are very scattered and concentrated on a certain period. The purpose of this study is to attempt to see the conditions in which the institution were established, the criticisms especially made after 1980 intensively to this institution that initiated under those conditions, who made the criticism on what grounds, why some of the continuous criticism points against the institution are still unanswered/ unresolved today, whether changes were made as a result of the critiques or not, and if so, for what reasons that changes are occur. The aim of this study is to endeavor to read, understand and interpret the criticisms made to the Presidency of Religious Affairs for various reasons. The importance of our work is revealed exactly here. When it comes to the Presidency of Religious Affairs and especially the criticisms made to it, it is seen that the studies are written in a biased language, far from being concerned about objectivity. The purpose of this thesis is to read, understand and try to interpret the criticisms directed to the Presidency of Religious Affairs for various reasons as a third eye. Therefore, for the sake of following the discussions about Presidency of Religious Affairs during the establishment period and in subsequent periods, this study will examine minutes of the parliament, institution's annual reports, internal and external correspondence, the reflections of the iii media (newspapers, newsletters, etc) about the discussions, and the other studies about the institution. By excavating the data in the literature, the criticisms that will be considered in the dissertation will be observed as much as possible in their real time and conditions, and the opportunity will arise to monitor and analyze how criticisms are interpreted by different groups that have found an area of existence in Turkish society.
Analysis on discourses on criticism of the institutional entity and legitimacy of the presidency of religious affairs
Keywords: Alevilik; Alevilik/ Alevism; Din ve devlet; Diyanet İşleri Başkanlığı; İslamcılık; İslamism; Kemalism; Kemalizm; Laiklik The Presidency of Religious Affairs; Religion and state; Turkey; Turkey. Diyanet İşleri Başkanlığı; Türkiye; Türkiye. Diyanet İşleri Başkanlığı